Posted by **israel** on Thursday, September 8, 2011 at 7:23pm.

y-abs(-2x/3x+1)

## Answer this Question

## Related Questions

- math - would this be a correct proof of the cauchy-schwartz inequality: abs=...
- maths complex numbers - Can abs(28-7w)=7abs(w) be written as abs(w-4)=abs(w) and...
- calc - Find the critical number(s) of f(x)= abs(2x-4) What is the derivative of ...
- calculus - Sketch the curve y = x^3 - 12x^2 + 36x I already did the question ...
- Absolute Value and Limits - solve for limits of 1+ and 1- for this function: (x^...
- math - So I need to solve this differential equation dy/dx = 1/(x+2) so i solved...
- Geometry - Show the conhecture is false by finding a counterexample... 1. The ...
- calculus - Find the slope of the curve at the indicated point. f(x)= abs(x) at a...
- Precalculus - The problem is: Rewrite f(x) = abs(x-2) + [2 * abs(x+5)] I don't ...
- math - Hi I Have A Question About Rolle's Theorem Why We cant solve [ F(x) = abs...